1995
DOI: 10.1111/j.1526-4610.1995.hed3501017.x
|View full text |Cite
|
Sign up to set email alerts
|

MMPI and Critical Flicker Frequency (CFF) Analysis in Headache Patients With and Without Drug Abuse

Abstract: Sixty-three headache patients (migraine: n = 28; tension-type headache: n = 35) who fulfilled the IHS criteria of 'drug abuse' were investigated by means of the Minnesota Multiphasic Personality Inventory (MMPI) and the Critical Flicker Frequency (CFF) analysis. The results were compared to those of 63 headache patients without drug abuse (matched-pair case-control study). With respect to the MMPI results, no statistically significant differences between patients with drug abuse and patients without drug abuse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…Our results showed that in Group E, mood disorders and psychiatric comorbidity were more frequent than Group C. To our knowledge, there is no other study comparing the MOH patients evolving from ETTH with the other chronic headache types according to psychiatric comorbidity, in literature. MOH has not been found to be associated with anxiety and mood disorders when compared with other primary headache subtypes (Kurman et al, 1992;Pfaffenrath et al, 1991;Schnider et al, 1995). However in the study of Mitsikostas and Thomas, depressive disorders were more prevalent in MOH patients (Mitsikostas and Thomas, 1999).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Our results showed that in Group E, mood disorders and psychiatric comorbidity were more frequent than Group C. To our knowledge, there is no other study comparing the MOH patients evolving from ETTH with the other chronic headache types according to psychiatric comorbidity, in literature. MOH has not been found to be associated with anxiety and mood disorders when compared with other primary headache subtypes (Kurman et al, 1992;Pfaffenrath et al, 1991;Schnider et al, 1995). However in the study of Mitsikostas and Thomas, depressive disorders were more prevalent in MOH patients (Mitsikostas and Thomas, 1999).…”
Section: Discussionmentioning
confidence: 86%
“…Psychiatric comorbid disorder and chronic pain syndrome may present together without sharing the same pathophysiological mechanisms. There are studies reporting that the endogenous analgesia system in CDH patient groups is altered and defective (Fusco et al, 1997; Hering et al, 1993; Sarchielli et al, 2001; Schnider et al, 1995; Siniatchkin et al, 1998; Srikiatkhachorn et al, 1994), also in experimental studies it has been shown that chronic use of analgesics may alter central 5‐HT system (Sandrini et al, 1993; Srikiatkhachorn et al, 2000). There are also studies reporting that muscle tension is higher in chronic pain patients with depression and depressed patients magnify the medical symptoms (Fishbain, 1999; Katon, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that the excess amounts of analgesics used lead to an increase in number of days with headache and a change in the characteristics of primary headache 3,4,10 . There are studies reporting that the endogenous analgesia system in CDH patient groups is altered and defective 11–14 . The hypothesis that chronic use of analgesics may alter central 5‐HT system has been supported by experimental studies 15,16 …”
mentioning
confidence: 99%
“…Using the critical flicker frequency (CFF) analysis, Schnider et al [20,21] showed that the vigilance or attentive system was impaired in the patients with analgesic abuse headache. They also demonstrated that the decreased CFF value became normalized after analgesic withdrawal.…”
Section: Neurophysiologic Evidences Supporting Central Mechanismmentioning
confidence: 99%